PENGEMBANGAN USAHATANI KOPI DI DESA KELAISI BARAT KABUPATEN ALOR - Marsalina B. T. Bekak; Gerson Hans Maure; Didiana Y. Molebila (JURNAL AGRIMANSION, 2025)
Coffee is one of the plantation commodities that has high economic value with a variety of distinctive flavors. This study aims to formulate the right coffee farming development strategy, in accordance with local potential and challenges. The study was conducted in Kelaisi Barat Village, Alor Selatan District, Alor Regency from April - May 2025. The method used in this study used a survey method with data processing assisted by SWOT analysis, IFAS Matrix and EFAS. The results obtained in this study were identified factors for formulating strategies based on internal factors and external factors located in quadrant I, namely in a favorable situation. Coffee farming development strategy in Kelaisi Barat Village, Alor Selatan District S-O: increasing quality coffee production for increasing market demand and utilizing organic coffee plants for good prices, W-O: maximizing traditional plant cultivation for good prices and maximizing land for increasing market demand, S-T: Maintaining price stability and maintaining traditional cultivation techniques for good coffee quality, W-T: improving cultivation techniques to improve coffee quality and increasing land optimally to obtain capital.